Emotion Regulation and Social Support in Deaf Adults: Empirical Findings from an Indonesian Sample - Rapika; Iftita Rahmi; Hanifa Laura Dalimunthe; Rahmadianti Aulia (Universitas Negeri Medan, 2026)
This study examined the contribution of social support to emotion regulation among deaf adults in Indonesia. A quantitative approach with a correlational research design was employed. The participants consisted of 122 deaf adults aged between 18 and 60 years who were selected using purposive sampling. Data were collected using the Social Support Scale and the Emotion Regulation Scale, which had demonstrated satisfactory validity and reliability. Data were analyzed using simple linear regression to determine the contribution of social support to emotion regulation. The findings revealed a significant positive contribution of social support to emotion regulation, indicated by a significance value of 0.004 (p < .05) and an R² value of 0.066. These results suggest that social support accounted for 6.6% of the variance in emotion regulation, while the remaining 93.4% was explained by other factors beyond the scope of this study. The findings indicate that deaf adults who receive greater social support tend to demonstrate better emotion regulation. This study highlights the importance of strengthening social support from families, peers, and communities while encouraging further research to identify other psychological and environmental factors that contribute to emotion regulation among deaf adults.